MODERNIZATION OF MULTI-APARTMENT BUILDINGS. WHAT’S WRONG? - Derkach, Sergii (Collection of scientific papers «ΛΌГOΣ», 2025)
Mass social panel residential buildings makes up a significant part of the housing stock in Ukraine. Predominantly, these are houses built according to projects of the 60s-80s of the 20th century. A similar situation is in other post-Soviet countries and others with the heritage of Soviet construction. Mass social housing has also been encountered in other countries of the world. Therefore, the renovation of old residential buildings is extremely important for every country. The issue modernization, with adopting a sustainable development agenda, has become particularly acute. This has identified the need to achieve sustainable urban development and energy efficiency, to reduce carbon emissions and preserve the environment. However, the renovation of old residential buildings and the creation of inclusive living conditions is an equally important topic.